Commodification and Shifting of Functions in the Tradition of Ngadatangkeun in Sundanese Society - Renic, Gemilang Yusrima; Syarif, Dede; Kurniasari, Dedeh (TEMALI : Jurnal Pembangunan Sosial, 2022)
This article discusses the shift in functions and forms of tradition in society. One of the essential functions of tradition for society is a symbolic function. This symbolic function is found through community involvement in traditional processions where they find meaning in solidarity and togetherness. However, the symbolic function of the tradition can actually be used to obtain non-symbolic interests such as achieving economic benefits. This research is focused on the Ngadatangkeun tradition in the Sundanese people in the Majalengka region, West Java. By using qualitative research methods with data collection techniques through participatory participation, interviews and literature review, this study argues that commodification has changed traditions' form and function from being symbolic to being materialistic. This commodification process has altered the symbolic social exchange in tradition into an economic function in the context of exchanging material (objects). This happens because the traditional procession has strongly emphasized aspects of material gain and private ownership as a form of materialistic attitude. This change is the background for the emergence of a new function in the Ngadatangkeun tradition, namely the economic function. However, the combination of symbolic functions and the development of new financial functions of tradition encourages tradition's duality, which complements each other rather than negates these functions.